Cryoballoon vs. radiofrequency catheter ablation: insights from NOrwegian randomized study of PERSistent Atrial Fibrillation (NO-PERSAF study). Issue 2 (19th November 2021) - Shi, Li-Bin; Rossvoll, Ole; Tande, Pål; Schuster, Peter; Solheim, Eivind; Chen, Jian
Abstract: Aims: Pulmonary vein isolation (PVI) is still regarded as a cornerstone for treatment of persistent atrial fibrillation (AF). This study evaluated the effectiveness of PVI performed with cryoballoon ablation (CBA) in comparison with radiofrequency ablation (RFA) in patients with persistent AF. Methods and results : A total of 101 patients with symptomatic persistent AF were enrolled and randomized (1:1) to CBA or RFA groups and followed up for 12 months. The primary endpoint was any documented recurrent atrial tachyarrhythmia (ATA) lasting longer than 30 s following a 3-month blanking period. Secondary endpoints were procedure-related complications, procedure and ablation duration, and fluoroscopy time. The ATA-free survival curves were estimated by Kaplan–Meier method and analysed by the log-rank test. According to intention-to-treat analysis, freedom from ATA was achieved in 36 out of 52 patients in the CBA group and 30 out of 49 patients in the RFA group (69.2% vs. 61.2%, P = 0.393). No difference in AF recurrence was found between the two groups (27.5% in CBA vs. 38.0% in RFA, P = 0.258), and less atrial flutter recurrence was documented in the CBA group compared with the RFA group (3.9% vs. 18.0%, P = 0.020). The procedure and ablation duration were significantly shorter in the CBA group (160 ± 31 vs. 197 ± 38 min, P < 0.0001; 36.7 ± 9.5 vs. 55.3 ± 16.7 min, P < 0.0001). There was no difference regarding fluoroscopy time (21.5 ± 7.8 vs. 23.4 ± 11.2 min, P > 0.05). Conclusion : Compared with RFA, PVI performed by CBA led to shorter procedure and ablation duration, with less atrial flutter recurrence and similar freedom from ATA at 12-month follow-up.